POSSIBILITIES OF ADVANCEMENT FOR SWEET PACKING INDUSTRY IN SERBIA AND ITS ADAPTATION FOR REQUIREMENTS OF OUR AND INTERNATIONAL MARKET - Stojanović, Vladimir (Economics of Agriculture, 2006)
Possibilities of advancement for sweet packing industry in Serbia are focused through disscusion of following questions: Possibilities and forms of vertical produced connection of manufecturers of raw material and sweet packing industry. Need for introduction of new and export product. Request for growth of food products and scientific-technical progress stir whole development of food industry, division of labour in the production of final food products on numerous branches, so some firms on the basis of the same raw material develop various lines of final products. Economic importance of sweet packing industry results from the fact that it lessens the season's character of agriculture, offers equally sweet packing products during the year and very effectively in the export of sweet packing products, performs the valorization of Serbian agricultural products on world market. Sweet packing firms introduce new products wishing to increase the efficiency of their distibutive systems and so they influence on potential competition.Attaing suitable renown on Serbian market, sweet packing industry creates possibility for futher development by the export of new product on the international market.